Hydrogen Bond Donor-promoted Fixation of CO2 with Epoxides into Cyclic Carbonates: Moving Forward - Wang, Jinquan (Current Green Chemistry, 2015)
Carbon dioxide (CO2) is not only an easily available, renewable carbon resource, but also an environmentally friendly chemical reagent. Fixation of CO2 with epoxides into cyclic carbonates (CC) is one of the most promising methodologies in this area. Recently, increasing attentions have paid to the utilization of environmentally benign hydrogen bond donors as the co-catalysts, and it is clear that hydrogen bond donors remarkably promote the reaction. In this review, we highlight the progress that have been made, and summarize the hydrogen bond donors (HBD) as co-catalysts for fixation of CO2 with epoxides into CC, and the results have been tabulated to summarize reaction conditions and catalytic activities for various typical epoxides conversions. Furthermore, the HBD-promoted reaction mechanism will also be summarized and discussed in details.
Keywords: mechanism